1998
DOI: 10.1074/jbc.273.46.30225
|View full text |Cite
|
Sign up to set email alerts
|

Elastase and the LasA Protease of Pseudomonas aeruginosa Are Secreted with Their Propeptides

Abstract: Pseudomonas aeruginosa elastase and the LasA protease are synthesized as preproenzymes with long amino-terminal propeptides. The elastase propeptide is cleaved autocatalytically in the periplasm to form a transient, inactive elastase-propeptide complex. In contrast, the processing of proLasA does not involve autoproteolysis. In this study, we analyzed short-term P. aeruginosa cultures under conditions that minimize proteolysis and found that an elastase-propeptide complex is secreted, and then the propeptide i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 34 publications
3
84
0
1
Order By: Relevance
“…3A) demonstrated that much less elastase protein accumulated in an 18-h culture supernatant of the dsbA mutant than in the wild type. As a test for the ability to secrete elastase protein, which may be unstable over time, washed cells were tested for the ability to release the protein after just 30 and 60 min into fresh medium as previously de- (18). Under these conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3A) demonstrated that much less elastase protein accumulated in an 18-h culture supernatant of the dsbA mutant than in the wild type. As a test for the ability to secrete elastase protein, which may be unstable over time, washed cells were tested for the ability to release the protein after just 30 and 60 min into fresh medium as previously de- (18). Under these conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The examination of elastase in stationary-phase culture supernatants using a Western blot analysis showed reduced levels of elastase, suggesting that the dsbA mutation compromised elastase accumulation. However, examination of 30-min washed-cell cultures, which can detect unstable secreted proteins (18), showed that elastase was secreted. Thus, the lack of elastase accumulation in the supernatant over time probably reflects its instability in the absence of proper folding by DsbA.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies have shown that HA/protease has bifunctional properties; the 45-kDa form is responsible for the enterotoxic response and the fully processed 35-kDa protease causes the HA activity responsible for the cytotoxic effects caused by this organism (10). We note that the processing of the pro-LasA to mature LasA protease in P. aeruginosa has been shown to involve the action of other secreted proteases, including elas-tase, lysine-specific protease (protease IV or PrpL), and alkaline proteinase (14). Kessler et al (14) showed that purified preparations of each protease were able to convert the secreted 42-kDa pro-LasA into the mature 20-kDa LasA, with the transient accumulation of a 28-kDa intermediate.…”
Section: Discussionmentioning
confidence: 99%
“…The pro-sequences of P. aeruginosa elastase (LasB) and Bacillus thermoproteolyticus thermolysin act as molecular chaperones that mediate folding of the mature enzymes within the periplasm (Braun et al, 1996;Marie-Claire et al, 1999;McIver et al, 1995;O'Donohue & Beaumont, 1996). The propeptides remain non-covalently associated with the mature enzymes to inhibit their proteolytic activity until liberation from the cell (Braun et al, 1998;Kessler & Safrin, 1994;Kessler et al, 1998;O'Donohue & Beaumont, 1996).…”
Section: Discussionmentioning
confidence: 99%